Analisis Kelimpahan dan Keanekaragaman Perifiton di Sekitar Karamba Jaring Apung Sungai Barito Kalimantan Selatan - Dharmaji, Dedy; Asmawi, Suhaili; Yunandar, Yunandar; Amalia, Intan (Rekayasa, 2021)
Perifiton whose life is attached to the substrate, acts as a provider of nutrients and indicators of fishery water quality. The purpose of this study was to analyze the structure, abundance and diversity of epiphytic and epidendric periphyton in floating net cages and water quality. This research was conducted by purposive sampling in upstream, middle and downstream. The method used is exploratory quantitative, from May and June 2021 with sampling time at the beginning of each month. The main phytoplankton periphyton composition consists of Chlorophyceae and Bacillariophyceae. Chlorophyceae increased from 19 genera at the beginning of the observation to 24 genera, while Bacillariophyceae decreased from 22 to 21 genera. Phytoplankton periphytons that were always present in each observation both at STA-1, STA-2 and STA-3 were Synedra, Diatoma, Tabellaria, Fragillaria, Zygnema, Spirogyra, Mougeotiopsis, Microspora, Chlorodesmis cosmosa and Closterium. Unstable community structure with an abundance of 600 – 1320 cells/liter, uniformity index 0.53 – 0.884, diversity index 1.104 – 1.750 and dominance index 0.14 -0.47 classified as oligotropic. Similar periphyton upstream and midstream, but different downstream. The presence of Synedra in all locations indicates that there has been a decline in water quality due to low dissolved oxygen. Water quality at the site informs that low pH, high ammonia and high organic matter result in low dissolved oxygen.